Al-Nahyu; Concept and Implementation in Islamic law Determination - Maulidizen, Ahmad; Sahida, Asphia (Khatulistiwa, 2019)
Usul Fiqh is the basis of the science of jurisprudence, which acts as a foundation in determining the law, classification of arguments as well as situations and conditions behind the existence of arguments. In the discussion of the Usul fiqh there is al-Nahyu, which has the meaning of prohibition in doing something that is prohibited by the Shari'a. This article will discuss the concept of al-Nahyu and its implementation in establishing Islamic law. The purpose of this discussion is to understand the way in which Islamic law is determined in accordance with what has been stated by ushul fiqh scholars in understanding the Koran and Hadith. This article is a literature study that uses the method of collecting data in documentation that comes from related reference materials such as books, journals and others. Then it is analyzed deductively, inductively and comparatively. There are Devision of Prohibition: Nahi shows that the law commits prohibited acts unless there are indications that indicate other laws, a prohibition on showing a facade (damaged) of an act that is prohibited if done, Nahi shows haram, Nahi shows a ban on something, an order for his opponent, Nahi shows an absolute prohibition, Nahi shows the prohibition on worship, Nahi shows a ban in mu'amalah.